Effect on Schottky Barrier of Graphene/WS2 Heterostructure With Vertical Electric Field and Biaxial Strain. Issue 10 (20th May 2019) - Zheng, Jiangshan; Li, Enling; Ma, Deming; Cui, Zhen; Peng, Tuo; Wang, Xiaolin
Abstract : Graphene has been widely used in many applications, such as sensors, field‐effect transistors, and integrated circuits due to its high strength and excellent electrical and thermal conductivity. Its lack of a band gap, however, means that applications in some fields are limited. In this paper, using first principles calculations based on the density functional theory method, the electronic properties of graphene/WS2 heterostructures under electric field and in‐plane biaxial strain are investigated. It is found that the two materials are subject to weak van der Waals forces after stacking. The band gap of WS2 in the graphene/WS2 heterostructure is reduced by 0.57 eV compared to the intrinsic WS2 band gap. An n ‐type Schottky contact with a barrier height of 0.22 eV is formed. In addition, an n ‐type to p ‐type Schottky contact transition can be achieved by increasing the applied vertical electric field on the graphene/WS2 heterostructure. The variation of the barrier heights ϕB n and ϕB p of the graphene/WS2 heterojunction with strain is sensitive. However, plane strain can only change the height of the Schottky barrier; the Schottky contact cannot change from n ‐type to p ‐type with in‐plane biaxial strain. The results suggest that there is a potential application of graphene/WS2 heterostructures in Schottky devices. Abstract : An n ‐type to p ‐type Schottky contact transition can be achieved by increasing the applied vertical electric field on the graphene/WS2 heterostructure. The variation of barrier heights ΦB n and ΦB p of the graphene/WS2 heterojunction with strain is sensitive. However, plane strain can only change the height of the Schottky barrier and cannot change the contact from n ‐type to p ‐type with in‐plane biaxial strain.